'Thoughts on private sector growth in Caricom' - Hall, Marshall ([CDB] [St. Michael]BB, 2008)
Focuses on the special problems of reducing trade preferences in bananas in order to highlight the breadth and depth of problems that are likely to confront the region as trade liberalization and globalization are expanded.